2021
DOI: 10.1136/rmdopen-2020-001379
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alcohol consumption and smoking on risk for RA: results from a Swedish prospective cohort study

Abstract: ObjectiveSeveral, but not all studies, have shown a dose-dependent inverse association with alcohol consumption and rheumatoid arthritis (RA), whereas smoking is an established risk factor for RA. We aimed to study the association between alcohol consumption and RA incidence and investigate a potential interaction between alcohol and smoking habits, regarding RA incidence.MethodsWe used a prospective cohort study, based on 41 068 participants with detailed assessment of alcohol intake, smoking and potential co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…To date, of the 10 prospective studies exploring alcohol consumption and RA risk, the majority (6 of 10) found no significant association between alcohol consumption and RA risk [ 8 , 15 , 27 , 28 , 29 , 30 ], whereas others found that moderate alcohol consumption was associated with a lower risk of RA [ 7 , 25 , 31 , 32 ]. One nested case-control study that matched on sex, reported sex-specific analyses of the association between alcohol consumption and RA risk [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, of the 10 prospective studies exploring alcohol consumption and RA risk, the majority (6 of 10) found no significant association between alcohol consumption and RA risk [ 8 , 15 , 27 , 28 , 29 , 30 ], whereas others found that moderate alcohol consumption was associated with a lower risk of RA [ 7 , 25 , 31 , 32 ]. One nested case-control study that matched on sex, reported sex-specific analyses of the association between alcohol consumption and RA risk [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the relationship between alcohol consumption and RA risk may be affected by a variety of confounding factors. Whereas smoking and certain genetic factors have been identified as factors that affect the relationship between alcohol consumption and RA risk [ 6 , 7 ], it is possible that there are cultural or socioeconomic factors that can also impact the association between alcohol consumption and RA. Accounting for confounding factors has been inconsistent in previous prospective cohort studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our past NHS cohort studies, and those from other populations, have shown that smoking and obesity were strongly associated with an increased risk of RA, in particular seropositive RA (7–9). We also found that more hours of recreational physical activity and healthier eating, as measured by the Alternative Healthy Eating Index (AHEI), were associated with reduced RA risk (10).…”
Section: Introductionmentioning
confidence: 97%
“…We also found that more hours of recreational physical activity and healthier eating, as measured by the Alternative Healthy Eating Index (AHEI), were associated with reduced RA risk (10). Moderate alcohol consumption (5.0–9.9 gm/day versus none) was associated with a reduction in RA risk (9,11).…”
Section: Introductionmentioning
confidence: 99%